Comparison of genetic variations between high- and low-risk Listeria monocytogenes isolates using whole-genome de novo sequencing - Ryu, Jihye; Choi, Yukyung; Yoon, Yohan (Frontiers in Microbiology, 2023)
In this study, genetic variations and characteristics of Listeria monocytogenes isolates from enoki mushrooms (23), smoked ducks (7), and processed ground meat products (30) were examined with respect to hemolysis, virulence genes, growth patterns, and heat resistance. The isolates that showed the highest pathogenicity were analyzed to obtain the whole-genome sequence, and the sequences were further analyzed to identify genetic variations in virulence, low-temperature growth-related, and heat resistance-related factors. All isolates had β-hemolysis and virulence genes (actA, hlyA, inlA, inlB, and plcB). At low temperatures, isolates with high growth (L. monocytogenes strains SMFM 201803 SD 1-1, SMFM 201803 SD 4-2, and SMFM 201804 SD 5-3) and low growth (L. monocytogenes strains SMFM 2019-FV43, SMFM 2019-FV42, and SMFM 2020-BT30) were selected. Among them, L. monocytogenes SMFM 201804 SD 5-3 showed the highest resistance at 60°C and 70°C. The strains SMFM 201804 SD 5-3 (high-risk) and SMFM 2019-FV43 (low-risk) harbored 45 virulence genes; 41 single nucleotide variants (SNVs) were identified between these two isolates. A comparison of 26 genes related to low-temperature growth revealed 18 SNVs between these two isolates; a comparison of the 21 genes related to heat resistance revealed 16 SNVs. These results indicate that the differences in the pathogenicity of L. monocytogenes SMFM 201804 SD 5-3 and L. monocytogenes SMFM 2019-FV43 are associated with the SNVs identified in virulence, low-temperature growth-related genes, and heat resistance-related genes.